1994
DOI: 10.2307/3431926
|View full text |Cite
|
Sign up to set email alerts
|

Exhaust Emissions from Light- and Heavy-Duty Vehicles: Chemical Composition, Impact of Exhaust after Treatment, and Fuel Parameters

Abstract: This paper presents results from the characterization of vehicle exhaust that were obtained primarily within the Swedish Urban Air Project, "Tätortsprojektet." Exhaust emissions from both gasoline- and diesel-fueled vehicles have been investigated with respect to regulated pollutants (carbon monoxide [CO], hydrocarbon [HC], nitrogen oxides [NOx], and particulate), unregulated pollutants, and in bioassay tests (Ames test, TCDD receptor affinity tests). Unregulated pollutants present in both the particle- and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…Sidestream smoke, the primary contributor to ETS, is known to be particularly rich in CHRYS and poor in BPer (IARC, 1979;Grimmer et al, 1987;Salomaa et al, 1988 ) as compared to diesel and gasoline combustion mixtures (IARC Monographs, 1983;Westerholm and Egeback, 1994 ). Although wood and coal combustion also results in CHRYS -rich PAH mixtures ( Cretney et al, 1985;Daisey et al, 1986 ) , these fuels are rarely used in Greece and the questionnaire data indicated that they were not used for residential heating of the study subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sidestream smoke, the primary contributor to ETS, is known to be particularly rich in CHRYS and poor in BPer (IARC, 1979;Grimmer et al, 1987;Salomaa et al, 1988 ) as compared to diesel and gasoline combustion mixtures (IARC Monographs, 1983;Westerholm and Egeback, 1994 ). Although wood and coal combustion also results in CHRYS -rich PAH mixtures ( Cretney et al, 1985;Daisey et al, 1986 ) , these fuels are rarely used in Greece and the questionnaire data indicated that they were not used for residential heating of the study subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The diversity of sources and PM 2.5 composition is also reflected in the variable strength of correlation between individual PAH and PM 2.5 ( Table 3 ), reflecting the variation of PAH composition of particulates emitted by different sources contributing to each subject's overall exposure. For example, BPer, which is a major component of the PAH associated with particulates produced by gasoline -driven motor vehicles (Westerholm and Egeback, 1994 ) and only a minor component in particulates originating from sidestream tobacco smoke (Grimmer et al, 1987 ) , showed the weakest association regardless of season and location. An additional factor, which probably contributes to variation in the correlation coefficients between PM 2.5 and PAH, especially the reduction observed during the summer for some PAHs (B [ a] A, CHRYS, and B[a ]P ) , may be the photoreactivity or the gaseous particulate distribution of these PAHs ( see further discussion below ).…”
Section: Variables Both Locations Athens Halkidamentioning
confidence: 99%
“…-Laboratory dynamometer test, which provides emission factors (EFs) for individual vehicles including gasoline/diesel light duty vehicles and heavy duty EFs (see e.g., Westerholm and Egeback, 1994;Sjögren et al, 1996;Hall et al, 2001;etc. ) -Car-chasing experiments and the FEAT-technique, provide EFs for individual vehicles in real world driving (Kittelson et al, 2000;Sjödin and Lenner, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Les gaz d'échappement de moteur diesel sont un mélange complexe se divisant en trois fractions : une phase solide, une phase condensée et une phase gazeuse (Westerholm & Egeback, 1994 ;Chan et al 2007). La phase solide PM (Particulate Matter) est majoritairement composée de particules carbonées primaires avec un noyau de carbone élémen-taire (EC) ou « carbone suie » de 10 à 30 nm de diamètre (Liati & Eggenschwiler, 2010).…”
Section: Gaz D'échappement De Moteurs Dieselunclassified